On the Rocks (A Ruby Steele Cozy Mystery-Book 1) - Mia, Gold (Lukeman Literary, 2020)
Ruby Steele, 30, beautiful, fit, seems just like any other ex-pat hiding out in the Bahamas and playing local bartender. But unruly patrons find out the hard way: Ruby is a mixed-martial-arts pro, and not one you'd want to cross.In fact, Ruby would be a champion if she hadn't been forced to walk away and hide out in the Bahamas.Because Ruby knows too much. She knows where the bodies are buried. And she knows when it's time to get out of town.But what Ruby doesn't know is why there is a dead tourist in the dumpster behind her seedy bar.Or why, she, of all people, had to find it.Or why this guy was out at 3am when he had a pretty fiancé waiting in a hotel room a mile away.Or why the local cops are pinning her.Or why she's gonna be forced into a choice: find the killer, or do hard time herself.For Ruby, good choices have never been her strong point.And this one's definitely not going to be good...Welcome to the Bahamian world of Ruby Steele, replete with her local dive bar, her wily pet monkey, her major drinking problem, her (way) too many fights, her inability to get herself out of trouble, and her fists made of stone. Ruby's life is a complete wreck. But there's one thing she's good at: capturing your heart.ON THE ROCKS (A RUBY STEELE COZY MYSTERY) is the debut novel in a page-turning cozy mystery/thriller series, one that will linger with you long after the last page is read. Books #2 (EXTRA DIRTY) and #3 (FULL-BODIED) in the series are also available.
Keywords: Krimi, detektivky